2014
DOI: 10.5152/balkanmedj.2014.13215
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ozone Therapy (OT) on Healing of Colonic Anastomosis in a Rat Model of Peritonitis

Abstract: Colonic resection and anastomosis is one of the most common operations in gastrointestinal surgery, both in children and adults. Although these are safe operations, an anastomosis leakage is a frequent problem (1, 2). Age, condition of the patient, colonic flora, inflammation and surgical techniques are the most important factors affecting the outcome of these procedures (3, 4). The presence of peritonitis is a defining factor of anastomosis integrity.The cecal ligation and puncture (CLP) model was first defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Ozone therapy has been used for infectious diseases such as conjunctivitis and keratitis ( 26 ), peritonitis ( 27 ), and surgical sepsis ( 28 ). In our clinical practice, topical application of ozone therapy is very effective for healing MRSA induced skin ulceration.…”
Section: Discussionmentioning
confidence: 99%
“…Ozone therapy has been used for infectious diseases such as conjunctivitis and keratitis ( 26 ), peritonitis ( 27 ), and surgical sepsis ( 28 ). In our clinical practice, topical application of ozone therapy is very effective for healing MRSA induced skin ulceration.…”
Section: Discussionmentioning
confidence: 99%
“…Ozone is a molecule which affects systemically 5 . It triggers reactions that affecting each other, when it is taken into the body.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, it was reported that ozone made a positive contribution to the healing of colonic anastomosis wound. Again, Erginel et al looked for the effect of ozone on colonic anastomosis wound healing in a rat model of peritonitis and stated that wound healing was better in the ozone treated groups, in their study 15 . It was determined that topical application of ozone had healing effects on acute skin wounds 16 .…”
Section: Discussionmentioning
confidence: 99%
“…An experimental study was performed on rats to assess the efficacy of ozone treatment in acute necrotizing pancreatitis 12 . Healing of colonic anastomoses with use of intraperitoneal ozone insufflation has also been studied 13 . It has also been shown to improve the distal colitis in an experimental study 14 .…”
Section: Resultsmentioning
confidence: 99%